Governing through vulnerability in austerity England - Menichelli, Francesca (European journal of criminology, 2021)
Drawing on interviews with practitioners, the article reconstructs how and why vulnerability has become an organizing principle in community safety work in England and Wales. Decreasing crime rates, growing awareness of risk and harm, loss of political salience of volume crime and modifications to the structure of incentives all contributed to making the move away from crime and disorder possible. The article shows how vulnerability is now used to facilitate partnership working to maintain existing levels of service provision, but also to ration the amount of support made available to citizens at a time of austerity. This is potentially problematic and open questions remain on the solidity, orientation and reach of this shift. The article concludes by discussing the research findings in light of their broader implications for European criminology and comparative research.